ONLINE LEARNING: A CHALLENGE FOR PARENTS (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out what challenges parents face in online learning and to what extent parents are ready for online learning to take place. The research method used is a systematic literature review (SLR). The results of the study show that the challenges faced by parents in online learning include time constraints, learning atmosphere, digital literacy, facilities and infrastructure, gender, children's social development, children's health, and parents' social status. The results of the study also show that parents are not ready for online learning to be implemented. Future research needs to look at parents' views on children's cognitive development in online learning and develop appropriate learning platforms so that teacher-student-parent communication can be well established in online learning